ANALISIS PENGARUH AUDIT TENURE, SPESIALISASI AUDIT, DAN REPUTASI AUDITOR TERHADAP KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI TAHUN 2011- 2015 - Saputro, Hendra Kusuma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study examines the influence of audit tenure, audit specialization, and audit reputation on audit quality, which is measured using Kazsnik’s model of discretionary accruals (1999), by including control variables such as client size, firm age, and operating cash flow. This study also examines the influence of control variables on audit quality. The population of this study is manufacturing companies working in basic and chemical industry listed in the Indonesia Stock Exchange during 2011-2015. Using purposive sampling method, this study has selected 180 financial statements. The results of multiple linear regression analysis applied in this study show that audit tenure, audit specialization, auditor reputation, client size, firm age, and operating cash flow simultaneously influence audit quality. The variables of audit tenure, audit specialization, and client size negatively influence audit quality. The variables of audit reputation and operating cash flow positively influence audit quality. However, firm age does not influence the audit quality in basic industries and chemical companies listed in the Indonesia Stock Exchange in the period of 2011-2015.Keywords: audit quality, audit tenure, audit specialization, auditor reputation, discretionary accruals